PEMBUATAN PAKAN IKAN AIR TAWAR DI POKDAKAN (KELOMPOK PEMBUDIDAYA IKAN) KARANG PIPA PLAJU DARAT - Desliyanah, Sherly; Aryani, Desi; Mahriadi, Nopriawan; Austin, Trecy (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2022)
The cultivation of fish is no longer a new thing in Indonesia. This is because there have been many pokdakans or Fish Cultivator Groups established. Pokdakan Karang Pipa Plaju Darat is one of them. There are many obstacles experienced by these fish cultivators, and the most crucial is the constraint of feed. 70% of fish farming activities depend on fish feed. The high price of manufactured feed makes fish cultivators nervous, where the costs incurred will be more than the profits they will get. The solution that has been offered by the government is the alternative use of independent fish feed. The socialization of the use of independent fish feed has been going on for a long time, but there has not been much interest, due to the lack of education or direct socialization to fish cultivators. Therefore, the community service team who collaborated with students, Stisipol Candradimuka carried out community service with a mandri fish feed making program. Where with this program, it can help fish cultivators to be able to make fish feed independently and be able to reduce fish feed expenditure.